Practicing What It Preaches? Understanding the Contradictions between Pluralist Theology and Religious Intolerance within Indonesiaâs Nahdlatul Ulama - Arifianto, Alexander R (Al-Jamiah: Journal of Islamic Studies, 2017)
The Nahdlatul Ulama (NU) has long been known for its moderate, pluralist theology. However, many grassroot NU clerics and activists do not pay attention to these pluralist teachings. Instead, they carried out attacks and religious persecutions against religious minorities such as the Ahmadi and Shiâite communities in Indonesia. It is puzzling to see a big contradiction between the pluralist theological beliefs articulated by some of NUâs senior clerics and the religiously intolerant actions conducted by many of its clerics and activists against religious minorities at a grassroot level. Using insights from social movement theory, this article argues that the roots of such contradictions can be traced back to NUâs organizational structure, which is decentralized and leave ultimate theological authority with local clerics who run their own Islamic boarding schools (pesantren) and issue their own theological interpretations and rulings (fatwa) that are being obeyed by their students and followers.[NU telah lama dikenal berteologi moderat dan pluralis. Meskipun demikian, ulama dan aktifis akar rumput kurang memperhatikan ajaran pluralis tersebut. Bahkan sebagian dari mereka justru terlibat dalam penyerangan dan persekusi kelompok minoritas seperti Ahmadiyah dan Shiah di Indonesia. Hal ini cukup membingungkan dan kontradiktif antara artikulasi pemikiran pluralis tokoh senior NU dengan tindakan intoleran yang dilakukan pengikut NU di level akar rumput. Dengan pendekatan teori gerakan sosial, artikel ini menjelaskan kontradiksi tersebut dengan melacak akarnya pada struktur organisasi NU yang terdesentralisasi dan otoritas teologi berbasis ulama lokal yang mempunyai pesantren dan interpretasi keagamaannya sendiri yang dipatuhi oleh santri dan pengikutnya.]